Pearson discover history book 2 (Karachi: Kifayat Publishers, 2024)
Pearson Discover History Book 2 explores major historical periods and civilizations from the classical era to the medieval world. It covers the rise and fall of influential empires such as ancient Greece and Rome, the expansion of Islamic civilization, the development of medieval Europe, and significant advancements in Asia and Africa. The book helps students understand how these civilizations shaped political systems, cultures, religions, economies, and global connections. Through timelines, primary sources, maps, and thought-provoking questions, students are encouraged to analyze historical events, compare societies, and recognize patterns of change and continuity. The book also emphasizes historical skills like critical thinking, inquiry, and evidence-based interpretation. Designed for lower secondary students, it provides a well-structured and engaging approach to learning world history during this key period.
Pearson Discover History Book 2 builds upon the foundational knowledge introduced in Book 1 and explores key historical developments from the classical civilizations to the medieval world. The book guides students through significant events, societies, and changes across different regions, including ancient Greece, Rome, early Islamic civilizations, medieval Europe, and Asian empires. With a focus on developing historical understanding, the book enhances skills such as interpreting sources, analyzing cause and effect, recognizing continuity and change, and comparing past societies. Each chapter is supported by engaging visuals, maps, timelines, and inquiry-based activities that encourage students to think critically and make connections between the past and present. Aligned with international curriculum standards, the book promotes independent learning, group discussion, and historical research. It aims to deepen learners$1 (Bappreciation for global history and foster a broader worldview.s
Keywords: Indus Valley Civilization; Early Human Societies